The Effect Of Evidence-Based Nursing Practices On Patient Recovery In Intensive Care Units- Systematic Review (The Review of Diabetic Studies, 2025)
PurposeThe aim of this study is to evaluate the impact of evidence-based nursing practices (EBP) on patient outcomes for ICU recovery such as infection prevention, pain, early mobility, and falls. It also tries to identify barriers and facilitators of implementing EBP in ICUs in an attempt to develop improvement strategies in patient care.Design/Methodology/ApproachA PRISMA-guided systematic review was conducted reviewing peer literature published between 2000 and 2022 in databases PubMed, Scopus, CINAHL, Cochrane Library, and Web of Science. Studies included were experimental, quasi-experimental, and observational EBP intervention designed in ICUs. Study design, interventions, patient outcomes, and implementation barriers were extracted from data with narrative synthesis performed due to heterogeneity in study design.FindingsFifteen trials with 4,320 ICU patients showed that EBP interventions had a significant impact on recovery outcomes. Infection control measures decreased hospital-acquired infections (e.g., 50% decrease in CLABSIs, p < 0.001), pain management interventions decreased pain severity by 25% (p < 0.05), early mobility decreased the length of ICU stay by 2.7–3.1 days (p = 0.01–0.03), and fall prevention strategies decreased fall rates by 20–30% (p = 0.03–0.05). Facilitators and barriersFacilitators were organized training and interprofessional collaboration, whereas barriers were time constraint, training, and leadership support.ConclusionEBP significantly enhances ICU patient recovery by reducing complications and improving care efficiency. Removal of barriers through focused interventions is essential for long-term implementation of EBP.Practical ImplicationsHealthcare institutions should invest in EBP training programs, standardized protocols, and leadership support to install infection control, pain management, early mobility, and fall prevention into ICU practice. This will improve patient outcomes, reduce healthcare expenses, and promote higher-quality care.